4‐(Di‐/Trifluoromethyl)‐2‐heterabicyclo[2.1.1]hexanes: Advanced Fluorinated Phenyl Isosteres and Proline analogues. Issue 47 (9th June 2021) - Homon, Anton A.; Hryshchuk, Oleksandr V.; Mykhailenko, Olha V.; Vashchenko, Bohdan V.; Melnykov, Kostiantyn P.; Michurin, Oleg M.; Daniliuc, Constantin G.; Gerus, Igor I.; Kovtunenko, Volodymyr O.; Kondratov, Ivan S.; Grygorenko, Oleksandr O.
Abstract: A gram‐scale synthesis, physico‐chemical characterization, and lead‐likeness assessment of 4‐di/trifluoromethyl‐2‐heterabicyclo[2.1.1]hexanes as fluorinated bicyclic proline analogues and phenyl isosteres are disclosed. The key step of the synthesis included iodocyclization of fluorinated 3‐hydroxy‐/3‐aminomethyl methylenecyclobutanes; with the amino derivatives, the reaction was accompanied with carboxylation and further cyclization. Apart from the corresponding 4‐di/trifluoromethyl‐2, 4‐methanoprolines, a series of fluorinated oxabicyclo[2.1.1]hexane‐derived building blocks relevant to medicinal chemistry (i. e. primary iodides, carboxylic acids, alcohols, azides, primary amines, sulfonyl chlorides, and alkynes) were prepared. For representative derivatives of the resulting fluorinated 2‐oxabicyclo[2.1.1]hexanes, p K a and log P values were measured to clarify their potential as the possible phenyl isosteres. Apart from the somewhat increased acidity, fine‐tuned lipophilicity intermediate between that of non‐fluorinated or aromatic counterparts was observed. Finally, the potential of the title building blocks was demonstrated by generation of virtual compound libraries using the LLAMA software. The resulting libraries fitted perfectly the lead‐like chemical space, had higher three‐dimensionality, and showed lower mean lead‐likeness penalty as compared to those obtained from either non‐fluorinated or aromatic derivatives. Abstract : A robust gram‐scale synthesis, physico‐chemical characterization, and lead‐likeness assessment of novel 4‐di/trifluoromethyl‐2‐heterabicyclo[2.1.1]hexane building blocks as fluorinated 2, 4‐methanoproline analogues and phenyl isosteres are disclosed.